THE PARASOCIAL CONTRACT: RE-ENGAGING THE DISTRIBUTED WORKFORCE THROUGH DIGITAL LEADERSHIP AND VIRTUAL EMPLOYER BRANDING - Priyata Westraperdana; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2026)
The shift toward distributed workforces has transformed employee–organization relationships, creating new challenges for maintaining engagement and connection in digitally mediated environments. Traditional approaches to engagement, rooted in physical proximity and direct interaction, are increasingly inadequate in remote contexts. This article introduces the concept of the “parasocial contract” as a novel framework for understanding how employees develop perceived connections with organizations through digital communication and virtual presence. Drawing on a conceptual and thematic review of literature on digital leadership, virtual employer branding, and employee engagement, the study explores how these elements can be leveraged to re-engage distributed employees. The findings suggest that digital leadership—characterized by communication, visibility, and authenticity—plays a critical role in fostering trust and connection. Similarly, consistent and credible virtual employer branding strengthens employees’ identification with organizational values and purpose. Together, these factors create a mediated yet meaningful form of engagement that can compensate for the absence of physical interaction. The study contributes to the evolving discourse on digital work by integrating insights from HRM and media theory. It concludes that organizations must strategically align leadership, branding, and technology to build sustained engagement in distributed work environments.